1986
DOI: 10.1002/crat.2170210603
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure Phase Transitions in the Perovskites A(Cu1−xMnx)Mn4O12(A = Na+, Ca2+, Y3+, La3+)

Abstract: Crystal Structure Phase Transitions in the PerovskitesA(Cul,Mn,)MnaOle(A = Na+, Cae+, Y8+, La8+) X-Ray diffraction and neutronographical studies on the crystal structure of the perovskitelike compounds A(Cu1 -zMnz)3Mn40,z have been undertaken. It has been shown t h a t the samples with 60% of Mn3+ in the octahedral sites have a cubic unit cell, while the samples with higher Mn3+ composition may have a monoclinic or rhombohedra1 unit cell. The temperature increase raises the symmetry to the cubic one. The conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Dielectric and resistivity (Supporting Information, Figure S15) data demonstrated that the reentrant transition is not accompanied by am etal-insulator transition. BiCu x Mn 7Àx O 12 [13] and similar solid solutions RCu x Mn 7Àx O 12 (R = rare earths) [14][15][16][17] exist up to x = 3. Pure BiMn 7 O 12 ,w hich has only the orbital degree of freedom from Jahn-Teller Mn 3+ cations,e xhibits symmetry lowering from Im3 to P1v ia two intermediate monoclinic phases during cooling.…”
Section: Zuschriftenmentioning
confidence: 98%
See 1 more Smart Citation
“…Dielectric and resistivity (Supporting Information, Figure S15) data demonstrated that the reentrant transition is not accompanied by am etal-insulator transition. BiCu x Mn 7Àx O 12 [13] and similar solid solutions RCu x Mn 7Àx O 12 (R = rare earths) [14][15][16][17] exist up to x = 3. Pure BiMn 7 O 12 ,w hich has only the orbital degree of freedom from Jahn-Teller Mn 3+ cations,e xhibits symmetry lowering from Im3 to P1v ia two intermediate monoclinic phases during cooling.…”
Section: Zuschriftenmentioning
confidence: 98%
“…Almost every composition with x 1.1 shows unique structural properties (Supporting Information, Table S4). BiCu x Mn 7Àx O 12 [13] and similar solid solutions RCu x Mn 7Àx O 12 (R = rare earths) [14][15][16][17] exist up to x = 3. We showed that the cubic Im3 structure is stable in the whole temperature range for x !…”
Section: Zuschriftenmentioning
confidence: 99%
“…14 Among the series, the structure of the compounds is cubic when there are Cu ions at AЈ position, such as NaCu x Mn 7−x O 12 , LaCu x Mn 7−x O 12 , and CaCu x Mn 7−x O 12 . 10,15,16 The charge ordering state is only observed in CaMn 7 O 12 ͑Mn 4+ :Mn 3+ =1:3͒ though the charge ordering state often takes place in Ln 1−x B x MnO 3 with Mn 4+ :Mn 3+ being 1:1. In this paper, we describe the preparation of PrCuMn 6 O 12 , its crystal structural transition from a trigonal phase to a cubic phase at 267 K accompanying disappearance of charge ordering.…”
Section: Introductionmentioning
confidence: 96%
“…It is worth to be noted that there is another family of manganese oxides with the general chemical formula [AC 3 ]B 4 O 12 where A = Ca 2+ , rare earth; B = Mn 3+ , Mn 4+ ; C = Mn 3+ or Cu 2+ [2,3]. In dependence on the nature of A and C cations the manganese valence changes from three to four.…”
mentioning
confidence: 99%
“…430 K [2]. Magnetic moments are oppositely aligned on C and B sites due to strong negative superexchange interaction between Cu 2+ and manganese [3]. The magnetotransport properties of this class of magnetic oxides were not reported earlier, so the purpose of this work is to study the electrical conductivity and magnetoresistance (MR) in these materials.…”
mentioning
confidence: 99%